Germanium-tin multiple quantum well on silicon avalanche photodiode for photodetection at two micron wavelength. (25th July 2016) - Dong, Yuan; Wang, Wei; Lee, Shuh Ying; Lei, Dian; Gong, Xiao; Loke, Wan Khai; Yoon, Soon-Fatt; Liang, Gengchiau; Yeo, Yee-Chia
Abstract: We report the demonstration of a germanium-tin multiple quantum well (Ge0.9 Sn0.1 MQW)-on-Si avalanche photodiode (APD) for light detection near the 2 μ m wavelength range. The measured spectral response covers wavelengths from 1510 to 2003 nm. An optical responsivity of 0.33 A W −1 is achieved at 2003 nm due to the internal avalanche gain. In addition, a thermal coefficient of breakdown voltage is extracted to be 0.053% K −1 based on the temperature-dependent dark current measurement. As compared to the traditional 2 μ m wavelength APDs, the Si-based APD is promising for its small excess noise factor, less stringent demand on temperature stability, and its compatibility with silicon technology.